Da admiração à obsessão: uma análise fílmica da série - MILLENA PAULA DO ESPIRITO SANTO (2024)
Admiration and obsession are latent concepts in fan culture. According to Barbosa and Braga (2022), admiration is a naive search for the subject, while an obsession refers to the reckless pursuit of the subject. The series Swarm (2023) narrates the story of Dre and her idol Ni’jah. It demonstrates how an admiring fan turned into a person obsessed with the artist. Swarm was critically acclaimed by receiving 87 points from critics and it is considered a subversive view of the toxicity of fandom (Rotten Tomatoes, 2023). Despite the popularity and relevance of the topic, there are no studies on Swarm. Therefore, this study aims to analyze Dre's admiration and obsession in the filmic narrative of “Swarm" (2023). After rigorous analysis, it was noted that admiration is portrayed as a genuine feeling that Dre has for Ni'jah and Marissa, but this becomes an obsession when she experiences losses.